Tuesday
March 28, 2017

Post a New Question

Posted by on .

a) Use the standard reduction potentials table to balance the following redox equation:

H2O2 + I + H = H2O + I2

b) Balance the following redox equation by the oxidation number method:

Ag + HNO3 = AgNO3 + NO + H2O

  • Chemistry 12 - ,

    I can't help you without doing all of the work. You need to learn how to do this yourself. What, specifically, do you not understand?

  • Chemistry 12 - ,

    i don't understand how i'm supposed to use the reduction potentials table to blance it

  • Chemistry 12 - ,

    To be completely honest, I don't understand that either since I've never been asked to use reduction potentials to balance a redox equation. However, I think it is done this way.
    Look up the standard reduction potential of H2O2 ==> H2O and I see the equation as follows (see +1.77 volts in the table):
    H2O2 + 2H^+ + 2e ==> 2H2O
    Then look up the I2 ==> I^- couple (see +0.535 volts) and I see the following:
    I2 + 2e ==> 2I^- but we want the reverse of that which is 2I^- ==>I2 + 2e, then we add the two together.
    H2O2 + 2H^+ + 2e ==> 2H2O
    2I^- ==> I2 + 2e
    -----------------------------
    H2O2 + 2H^+ + 2I^- +2e ==> 2H2O + I2 + 2e
    Check that I didn't make a typo in getting all of this down. Apparently one positive for this method is that a look at the standard reduction tables gives you the half reaction ALREADY balanced, then you balance the electrons (they are already ok in this example) and add them.
    For the oxidation number method, here is a very good site. Post with specific questions if you still have questions and I'll be happy to help you through them.
    http://www.chemteam.info/Redox/Redox.html

  • Chemistry 12 - ,

    wow thank you very much, that site is very helpful and you've been very helpful! Thank you!

  • Chemistry 12 - ,

    how are we supposed to add them together when there is no I in the first equation?

  • Chemistry 12 - ,

    You are adding the two halves. You add the H2O2 + 2H^+ + 2e ==> 2H2O which is the first half, then you place the second half below it (as I've done in my previous post) which is
    2I^- ==> I2 + 2e and add those two halves together to obtain the final of
    H2O2 + 2H^+ + 2I^- ==> 2H2O + I2

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question